EFEKTIVITAS PENGGUNAAN MEDIA GAMBAR BERSERI DALAM MENULIS EKSPOSISI SISWA KELAS V MADRASAH IBTIDAIYAH NAHDLOTUR RIZAL KROYA INDRAMAYU - Nuryani Nuryani; Abdur Rahim (JOEL: Journal of Educational and Language Research, 2022)
In the literature, it is known that there are many ways that can be used to make it easier for students to write expositions in learning Indonesian, but the effectiveness of each varies, depending on the creativity of teachers and students. This study aims to determine the effectiveness as well as the factors that support and inhibit the use of serial image media in learning to write exposition for fifth grade students of MIS Nahdlotur Rizal Kroya, Indramayu, Odd Semester for the Academic Year 2019/2020. The type of research used in this study is a qualitative research with an experimental qualitative approach, with the research subjects of 23 students of class V MIS Nahdlotur Rizal consisting of 8 women and 15 men. The research method used is observation, interviews, and documentation, besides that the researchers also conducted experiments with the type of case study, which was strengthened by interviews with teachers and students. The results showed that the use of picture series media can increase students' ability in writing expositions; if before using the picture series media, the student's writing skill (KKM) mastery achievement of exposition essays was 45% or below the classical minimum standard set (70%), then after using picture series media, the student's KKM achievement of exposition essays became an average 90% or above the standard (70%). The supporting factor for the use of serial picture media is the enthusiastic attitude of students, while the inhibiting factor in the use of serial picture media is the lack of teacher creativity due to the teacher's lack of experience in teaching.